Ideologi Pendidikan melalui Pendidikan Seni Musik dalam Sebuah Kreativitas - Laila Fitriah; Yofi Irvan Vivian (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2022)
Abstract: Education is one of the efforts to optimize human potential. One of the educational efforts to optimize students' potential is through music education. This research aims to see if teachers can utilize their culture and art (traditional music) as a form of education. Teachers must understand and apply educational ideology in supporting creativity in art education, especially traditional music. This study uses a qualitative descriptive method with a phenomenological approach. Education as an enculturation channel in the philosophy of education has at least three important roles: education as cultural conservation, education as cultural regression, and education as a cultural transition. Teachers or educators can be creative by correlating their cultural ownership with the three important roles of education. Through the education unit level curriculum (KTSP), the government has begun to provide space for the development of Indonesian arts (culture) education, which has been marginalized from the younger generation's lives.   Abstrak: Pendidikan menjadi salah satu usaha untuk mengoptimalkan potensi manusia. Salah satu upaya pendidikan untuk mengoptimalkan potensi siswa adalah melalui pendidikan seni musik. Tujuan penelitian ini diharapkan guru mampu memaksimalkan kebudayaan dan seni (musik tradisi) yang dimiliki  sebagai sarana pendidikan  Guru harus mampu memahami dan menerapkan ideologi pendidikan dalam menunjang kreativitas pada pendidikan seni, khususnya musik tradisional. Penelitian ini menggunakan metode deskriptif kualitatif, dengan pendekatan fenomenologi. Pendidikan sebagai saluran enkulturasi dalam filsafat pendidikan setidaknya memiliki tiga peranan penting, yaitu: education as cultural conserveation, education as cultural regression, dan education as cultural transition. Guru atau pendidik bisa berkreasi dengan mengkorelasikan kepemilikan budaya yang dimilikinya dengan ketiga peran penting dari pendidikan. Melalui kurikulum tingkat satuan pendidikan (KTSP), pemerintah mulai memberikan ruang bagi pengembangan pendidikan seni (kebudayaan) nusantara yang selama ini termarginalkan dari kehidupan generasi muda